ANALISIS KADAR ION BESI (Fe2+) DAN ION TIMBAL (Pb2+) DALAM IKAN MAKAREL KEMASAN KALENG BERDASARKAN LAMA WAKTU PENYIMPANAN - Dessy Karlina; Alimuddin Alimuddin; Chairul Saleh (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2019)
Analysis of iron ion (Fe2+) and lead ion (Pb2+) content in canned mackerel based long storage time has been investigated. The content of iron ion (Fe2+) and lead ion (Pb2+) has been analysed used the instrument Atomic Absorption Spectrophotometer (AAS). Based on long storage time result analysis of the content of iron ion (Fe2+) in canned mackerel the lowest is 2,71 mg/Kg with long storage time of 33 month and the highest is 5,21 mg/Kg with long storage time of 9 month while the result analysis of lead ion (Pb2+) in canned mackerel is not detected. Based on the result conclude is long storage time not affect the levels iron ion (Fe2+) and lead ion (Pb2+) in canned mackerel.